Succinylcholine versus rocuronium for rapid sequence intubation in intensive care: a prospective, randomized controlled trial - Stephan Märsch; Luzius A. Steiner; Evelyne Bucher; Hans Pargger; Martin Schumann; Timothy Aebi; Patrick Hunziker; Martin Siegemund (2011)
Abstract Introduction Succinylcholine and rocuronium are widely used to facilitate rapid sequence induction (RSI) intubation in intensive care. Concerns relate to the side effects of succinylcholine and to slower onset and inferior intubation conditions associated with rocuronium. So far, succinylcholine and rocuronium have not been compared in an adequately powered randomized trial in intensive care. Accordingly, the aim of the present study was to compare the incidence of hypoxemia after rocuronium or succinylcholine in critically ill patients requiring an emergent RSI. Methods This was a prospective randomized controlled single-blind trial conducted from 2006 to 2010 at the University Hospital of Basel. Participants were 401 critically ill patients requiring emergent RSI. Patients were randomized to receive 1 mg/kg succinylcholine or 0.6 mg/kg rocuronium for neuromuscular blockade. The primary outcome was the incidence of oxygen desaturations defined as a decrease in oxygen saturation ≥ 5%, assessed by continuous pulse oxymetry, at any time between the start of the induction sequence and two minutes after the completion of the intubation. A severe oxygen desaturation was defined as a decrease in oxygen saturation ≥ 5% leading to a saturation value of ≤ 80%. Results There was no difference between succinylcholine and rocuronium regarding oxygen desaturations (succinylcholine 73/196; rocuronium 66/195; P = 0.67); severe oxygen desaturations (succinylcholine 20/196; rocuronium 20/195; P = 1.0); and extent of oxygen desaturations (succinylcholine -14 ± 12%; rocuronium -16 ± 13%; P = 0.77). The duration of the intubation sequence was shorter after succinycholine than after rocuronium (81 ± 38 sec versus 95 ± 48 sec; P = 0.002). Intubation conditions (succinylcholine 8.3 ± 0.8; rocuronium 8.2 ± 0.9; P = 0.7) and failed first intubation attempts (succinylcholine 32/200; rocuronium 36/201; P = 1.0) did not differ between the groups. Conclusions In critically ill patients undergoing emergent RSI, incidence and severity of oxygen desaturations, the quality of intubation conditions, and incidence of failed intubation attempts did not differ between succinylcholine and rocuronium. Trial Registration ClinicalTrials.gov, number NCT00355368 .